Interactive effects of environment, management and mortality on cattle productivity in livestock systems in sub-Saharan Africa - Leeuw, P.N. de (University of Utrecht, 1990)
Analyses the productivity of different livestock production systems in sub-Saharan Africa and compares the output with higher-input ranching systems in similar environments to indicate potential improvements in productivity in response to better feeding, management and health care. Gives emphasis to the role of mortality and factors that influence death rates and examines effects of drought and discusses the consequences of the losses.